Driving Sustainable Growth: The Corporate Sustainability Due Diligence Directive as a Catalyst (CSDDD) for Public Administration Reform and Corporate Accountability in the European Green Deal - Butt, Junaid Sattar; Kousar, Farzana (The Journal of Accounting and Management, 2024)
The European Union (EU) has enacted a comprehensive set of sustainable finance laws, including the Sustainable Finance Disclosure Regulation (SFDR), the Taxonomy Regulation, and the Corporate Sustainability Due Diligence Directive (CSDDD) (Savourey & Litwin, 2024). This study explores the role of the (CSDDD) entered into force on July 25, 20243 as a catalyst for driving sustainable growth through the reform of public administration and the enhancement of corporate accountability within the context of the European Green Deal. The research aims to identify synergies between the CSDDD and the Green Deal, contributing to the discourse on sustainable economic development by providing a comprehensive understanding of how effective governance mechanisms can promote sustainability goals across the European Union. To achieve this, the study employs a mixed-methods approach that combines qualitative analyses of policy frameworks and quantitative assessments of economic outcomes in EU member states. Data were collected through case studies, interviews with stakeholders, and a review of existing literature on public administration reforms and corporate governance practices. The findings reveal that the implementation of the CSDDD significantly influences public administration reforms by fostering a culture of accountability and transparency in corporate practices. Furthermore, the study highlights that aligning corporate accountability measures with the objectives of the European Green Deal leads to improved environmental and economic outcomes, reinforcing the interconnectedness of sustainability and governance. In conclusion, this research underscores the critical need for coherent policy frameworks that integrate the CSDDD and the European Green Deal, emphasizing the importance of public administration reforms in facilitating corporate accountability. The broader implications suggest that fostering a collaborative governance approach can enhance sustainable economic growth while addressing pressing environmental challenges in Europe.